2005
DOI: 10.1111/j.1442-2050.2005.00489.x
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of glucose transporter 1 in esophageal squamous cell carcinomas: a marker for poor prognosis

Abstract: Recently, Glut1 (human erythrocyte glucose transporter) expression has been demonstrated in various tumors. The aim of this study is to evaluate the prognostic utility of Glut1 expression in esophageal carcinomas. We studied Glut1 expression by immunohistochemistry of paraffin sections from 63 esophageal squamous cell carcinomas. All 63 carcinomas expressed Glut1. The mean percentage of positively stained tumor cells was 77.8% (median, 84.7%). There were two staining patterns in positive cells: 'strongly posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
38
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 16 publications
7
38
0
Order By: Relevance
“…The multivariate analysis showed that GLUT-1, the number of chemotherapy courses and clinical M stage were independent prognostic factors for RFS. Previous studies found that the GLUT-1 over-expression in esophageal carcinoma is a risk factor for mortality (19,20) The results of these authors, together with our results, suggest that GLUT-1 expression is predictive of clinical outcomes in patients with esophageal carcinoma treated with CRT.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…The multivariate analysis showed that GLUT-1, the number of chemotherapy courses and clinical M stage were independent prognostic factors for RFS. Previous studies found that the GLUT-1 over-expression in esophageal carcinoma is a risk factor for mortality (19,20) The results of these authors, together with our results, suggest that GLUT-1 expression is predictive of clinical outcomes in patients with esophageal carcinoma treated with CRT.…”
Section: Discussionsupporting
confidence: 69%
“…Moreover, the percentage of patients with N1 tumor was significantly higher in the high GLUT-1 expression group than that of patients with a low GLUT-1 expression. A number of studies found an association between GLUT-1 expression and tumor stage (19,20). Tohma et al found that pathological T3-4 esophageal cancers showed higher percentages of GLUT-1 strong positive cells than T1-2 cancers, and lesions exhibiting lymph node metastasis showed higher percentages of GLUT-1 strong positive cells than lesions without lymph node metastasis (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported that the expression of Glut-1 correlates with 18F-fluorodeoxyglucose uptake and hence the PET image intensity of gastric cancer [4]. Furthermore Glut-1, is a negative prognostic factor for several types of cancer, such as lung cancer, rectal cancer, breast cancer, and esophageal cancer [5][6][7][8]. Glut-1 is also associated with an inferior prognosis in gastric cancer [9].…”
Section: Introductionmentioning
confidence: 99%
“…GLUT1 is highly overexpressed in many types of cancer cells [63] including brain [64], breast [65], cervical [66], colorectal [67], cutaneous [68], endometrial [69], esophageal [70], hepatic [71], lung [72], oral [73], ovarian [74], pancreatic [75], prostate [76] and renal [77]. Because cancer cells have an altered metabolism and an increased demand for nutrients they usually show an upregulation of GLUT1 in order to provide an enhanced uptake of glucose in correlation with a greater rate of glycolysis.…”
Section: -O-methyl-d-glucose; (Iii) 2-deoxy-2-fluoro-d-glucose (Fdg)mentioning
confidence: 99%